DC to DC regulator / Zainuddin Ab Rahman and Muhammad Shahril Othman - Ab Rahman, Zainuddin; Othman, Muhammad Shahril (2005)
The circuit present here is regulator or variable output power supply. This is part of power supply from DC to DC converter. For this part, components in this circuit work as to give the output from transformer which is to step down the AC supply and send to filter for change into DC which used for input in the variable output power supply. This regulation is ideal for having a simple variable bench power supply. Actually quite important because one of the first projects a hobbyist should undertake is the construction of a bench supply. While a dedicated supply is quite handy e.g. 1.2 to 11.5, it's much handier to have a variable supply on hand, especially for testing. That is why the variable is produce in this project. This is for easy to costumer for used their device in variable input supply.